Exploring the Impact of Work Relationships on Employee Performance - Panjinata, Awan; Suyono, Joko; Tobing, Bonardo Aldo; Widjanarko, Bambang; Elisabeth, Damarsari Ratnasahara (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The purpose of this study is to analyze the correlation of work relationships, and employee performance with job satisfaction as an intervening Design/methodology/approach: The population in this study were all production employees of pallet plastic industries in Sidoarjo,east java with 36 people. Data collection in this research used a questionnaire.and Data analysis in this research uses Partial Least Squares (PLS). Findings: The result that work relations affect employee performance with job satisfaction as an intervening variable. Research limitations/implications: This research is limited to doing regional pallet plastic industries in sidoarjo east java, Indonesia. For generalization so that further research can be carried out in different organizations or companies and in different regions (cities) Practical implications: The results of this research can be used as a reference to improve of employee performance in pallet plastic industries or similar plastic industries. Originality/value: The research results explain that among the variables work relationships, job satisfaction must be applied for increase of employee performance in pallet plastic industries or similar plastic industries.